THE ROLE OF FOOD DELIVERY APPLICATIONS IN INCREASE MSME SALES IN TAMALANREA DISTRICT - Nawir, Fadliyani; Meyfani, Ashari; Madrianah, Madrianah; Muchsidin, Murdin (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
This research aims to examine the role of food delivery applications in increasing the sales of Micro, Small, and Medium Enterprises (MSMEs) in Tamalanrea District. The main focus of this study is to understand how digital food delivery services like GoFood and GrabFood can help MSME actors expand their market reach and encourage business growth amidst a shift in consumer behavior toward application-based services. The method used in this research is a qualitative approach with a case study method, and the analysis is conducted inductively, by identifying general patterns from field data to obtain a more comprehensive and contextual understanding of the phenomenon being studied. The results show that food delivery applications have a significant impact on the growth of MSME sales. These applications are considered effective in supporting the digitalization of MSMEs, increasing competitiveness, and encouraging business adaptation toward a more professional and modern direction.